Pengaruh literasi ekonomi terhadap perilaku konsumtif siswa SMP Islam Bustanul Hikmah - Laili, Wulan Nur; Ghofur, Abd.; Rachma, Evi Aulia (PPPM STKIP PGRI Lamongan, 2023)
This research aims to determine the influence of economic literacy on the consumer behavior of Bustanul Hikmah Lamongan Islamic Middle School students. Apart from that, the aim of this research is to determine the economic literacy and consumer behavior of Bustanul Hikmah Islamic Middle School students. This research uses a quantitative research design. The sample for this research was 60 respondents from Bustanul Hikmah Lamongan Islamic Middle School students. Meanwhile, sampling uses purposive sampling or nonprobability sampling techniques, which is a type of random sample selection obtained using certain considerations, usually adjusted to the research objectives. Testing research instruments with validity and reliability tests. The results of the hypothesis test can be concluded that the Economic Literacy variable (X) has an effect on the Student Consumptive Behavior variable (Y). This can be seen from the calculated t value for the variable of 33.910 > 1.672 from the T table, so it can be concluded that the Economic Literacy variable (X) has an effect on the Student Consumptive Behavior variable (Y). And based on the significance value from the Coefficient table, the significance value obtained is 0.000 <0.05, so it can be concluded that the Economic Literacy variable (X) influences the Student Consumptive Behavior variable (Y).